Firearm Involvement of Parents and Their Adolescent Children: A Prospective Intergenerational Study of High-Risk Youth, Chicago, Illinois, 1995-2022 - Teplin, Linda A. ([Verlag nicht ermittelbar], 2022)
This study contains data from the Northwestern Juvenile Project (NJP) series, a prospective longitudinal study of the mental health needs and outcomes of youth in detention. The research team interviewed participants from the Northwestern Juvenile Project (NJP) (originally enrolled as they entered the Cook County Juvenile Temporary Detention Center from 1995 to 1998, and now parents ages 34-43 years) and their oldest child age 10 to 17 years when sampled, and leveraged data already collected on parents' firearm involvement--during their own adolescence and young adulthood for the NJP.